Analysis of concentration-dependent effects of thiopurines and thionucleosides on levels of reactive oxygen species in K562 cells - Albasri, Sajjad; Sysa, Aliaksei G.; Kvasyuk, Eugenii I.; Lemiasheuski, Viktar A. (Journal of the Belarusian State University. Chemistry, 2025)
Thiopurines and their nucleoside derivatives are widely used in cancer treatment, particularly for leukemia. However, their precise mechanisms of action, especially concerning reactive oxygen species (ROS) production, remain incompletely understood. This study investigated the effects of 6-mercaptopurine, 6-thioguanine, 6-thioguanosine, and 2′-deoxy-6-thioguanosine on ROS levels in K562 human chronic myelogenous leukemia cells. Using a 2′,7′-dichlorodihydrofluorescein diacetate essay, we measured ROS production across a concentration range of 10–6 to 10–4 mol/L. Our results revealed distinct patterns of ROS induction among the compounds. 6-Mercaptopurine showed a concentration-dependent increase in ROS levels, while 6-thioguanine exhibited a biphasic response with higher ROS production at lower concentrations. The nucleosides 6-thioguanosine and 2′-deoxy-6-thioguanosine demonstrated less pronounced effects on ROS levels. These findings provide valuable insights into the structure-activity relationships of thiopurines and thionucleosides, highlighting the complex interplay between their molecular structures and ROS-inducing properties. Our study contributes to a better understanding of the mechanisms underlying the anticancer effects of these compounds and may inform the development of more targeted and effective thiopurine-based therapies.
Keywords: thiopurines; reactive oxygen species; ROS; K562 cells; anticancer activity; structure-activity relationships; 6-thioguanine; 6-thioguanosine